Kinetics of reactive extraction/in situ transesterification of rapeseed oil - Zakaria, Rabitah; Harvey, Adam P. (Elsevier, 2014)
The kinetics of “reactive extraction” or “in situ transesterification” of rapeseed with methanol to produce biodiesel were investigated. It is hypothesised that in situ transesterification occurs through the reaction of triglyceride and methanol inside the seed particles followed by diffusion of mono and diglycerides, esters and glycerol into the bulk solvent. A model was developed based on this reaction/extraction mechanism and was found to be generally consistent with experimental results. The effective diffusion coefficient of esters in methanol was found to be 3.5 × 10− 12 m2/s. The model reveals that at catalyst concentrations below 0.1 mol/kg-solvent, the reactive extraction rate was controlled by the reaction of triglycerides to esters. However, at higher catalyst concentrations (> 0.1 mol/kg-solvent), the process was controlled by the rate of diffusion of the products. The diffusion coefficient increases linearly with increasing temperature and the temperature dependence of the reaction rate constants can be described by an Arrhenius relationship. External mass transfer does not influence the extraction rate at the conditions used in these experiments.